Saturday

February 28, 2015

February 28, 2015

Posted by **Anneliese** on Wednesday, February 25, 2009 at 2:39pm.

2x - 3y + 6z = -12

5x + 2y - 8z = 29

7x + 6y + 4z = 49

First, I did elimination for the first two equations. I multiplied the first equation by two, and the second equation by 3.

4x - 6y + 12z = -24

+

15x + 6y - 24z = 87

That gets me:

19x - 12z = 63.

The next thing I have written down that the teacher told us is:

11x + 16z = 25

How did my teacher get to this point?

Thanks!

- Algebra -
**Damon**, Wednesday, February 25, 2009 at 4:59pmcombine twice the top one and the bottom one

4 x - 6 y + 12 z = -24

7 x + 6 y + 4 z = +49

------------------------

11 x + 0 + 16 z = 25

- Algebra -
**Damon**, Wednesday, February 25, 2009 at 5:07pmIn the end

x = 3

y = 5

z = -.5

**Answer this Question**

**Related Questions**

algebra - Gina wrote this system of linear equations: 2x + y = 7 4x + 5y = 11 ...

Algebra - Suppose a linear system of equations has 2012 equations and 2013 ...

Algebra - To solve the following system of equations by elimination, which step...

Algebra - solving linear equations w/ substitution - The question in the book ...

Algebra 2 - 1.) Write a system of equations that has NO solution. 2.) If you ...

Algebra 2 - 1.) Write a system of equations that has NO solution. 2.) If you ...

Algebra 2 - 1.) Write a system of equations that has NO solution. 2.) If you ...

linear algebra - Use an inverse matrix to solve each system of linear equations...

linear algebra - Use an inverse matrix to solve each system of linear equations...

linear algebra - Use an inverse matrix to solve each system of linear equations...